midterm 2 take home

By integration by parts we have tx et dt u tx dv u

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 4) : Start with the indefinite integral tx e−t dt . u dv Here, treat x as a constant. By “integration by parts”, we have tx e−t dt u tx · dv = u − e−t − v x tx−1 dt v − e−t du . In other words, tx e−t dt x tx−1 dt − e−t + = = tx · − e−t +C − tx e−t + C . The corresponding definite integral: t t=0 +∞ +∞ +∞ x −t e dt −t + t=0 −e 10 xt x−1 dt = x −t −t e t=0 . That is, (♥) +∞ +∞ +∞ tx e−t dt − x t=0 tx−1 e−t dt − tx e−t = t=0 t=0 . Explain why the right-hand side of (♥) equals 0. Your explanation must involve the limit lim tx e−t . t− ∞ → Hence +∞ t=0 +∞ tx e−t dt − x tx−1 e−t dt = 0. t=0 Finally, rewrite this last identity using Γ x and Γ x + 1 . (5) (Extra 20pts) Let Γ x ln Γ x be as in (3). Know that ln Γ x = lim − γ + n− ∞ → − ln x 1+x n 1 x k k=1 1+ has the following expression: x 2 1+ x 3 · ··· · 1+ x n where γ is the Euler’s constant . One way to define the Euler’s constant γ is 11 , +∞ γ = − Γ′ 1 = t=0 e−t dt. − ln t Let f x and g x be as before page 4 . From the above expression of ln Γ x and the result of (4), one can prove −f x +g x = 1−γ x− ln Γ 2 + x , f x +g x = 1−γ x+ ln Γ 2 − x . Or, equivalently, fx = 1 2 gx = 1−γ ln Γ 2−x Γ 2+x x− 1 2 , Γ 2+x ln . Γ 2−x Use the above information to evaluate each of the following: ∞ (5a) m=2 −1 ∞ (5c) m=2 −1 m−1 m−1 ζm −1 m ζm −1 m · 2m ∞ , (5b) m=2 ∞ , (5d) m=2 The answers may involve γ . 12 ζm −1 m , ζm −1 m · 2m ....
View Full Document

Ask a homework question - tutors are online